Overlaying Landscapes:Refiguring public as interspecies cohabitation - Abrantes, Eduardo; Samson, Kristine (2022)
Amager Commons (Amager Fælled) is an urban recreational area and nature resort close to Copenhagen city centre which stretches over circa 2.5 km2, curiously nearly the exact same area as Reykjavík city centre, understood as a section of the most popular areas of the Vesturbær and Miðbær districts. Defined as an entangled space with a complex history of being a pasture for grazing, a shooting ground for the military and today a contested site under threat from urban development, it affords an abundance of inhabitation and lifeforms. From daily up-keep such as jogging, biking, dog walking and fishing, to the pursuit of specialised interests such as birdwatching, motocross, drone flying, plant gathering and neopaganism, to the intimate rituals of casual sex, psychotropic trips, picnics and birthday celebrations. Furthermore, Amager Commons, being both prime real-estate and a diverse yet vulnerable ecosystem, is one of Copenhagen’s most intensely debated and disputed sites – a place of friction between a plethora of stakeholders: from urban development to environmental activism, from municipal policies to citizens everyday practices. Nor have the multiple species living and breeding in the commons remained aloof from this conflict. The issues of sustainability, habitat protection and interspecies relations – with the inevitable discussions of preservation vs. cohabitation, degrees of post-human agency, and so on – have brought birds, bats, fish, insects and amphibians into the fray. Through a performative sonic walk we propose to fold the sites and weave the landscapes of Amager Commons together with the urban fabric of central Reykjavík, creating a hybrid collective experience of embeddedness and displacement. We will overlay Amager Commons through various sonic territories, allowing participants to encounter the commons with its various practices, lifeforms and frictions in the streets of Reykjavík. Here, environmental soundscapes will intersect with the streetscape to create a reconfiguration of public space that ...